2015
DOI: 10.1002/2327-6924.12223
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing breast cancer screening and risk assessment among young African American women: An integrative review of the literature

Abstract: Purpose This integrative review was conducted to examine factors that influence mammography screening and use of cancer genetic services among younger African American women at increased risk for developing breast cancer. Data sources Research articles were identified using PubMed, CINAHL, PsychINFO, and Cochrane library to find studies published from 2003 to 2013. Conclusions Findings from this review indicate that while younger African American women receive mammograms more often than the general population,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…A lack of medical insurance has been found to be a barrier to breast cancer screening participation in recent reviews10 14 39; however, evidence regarding medical insurance as a predictor of breast cancer screening participation was weak in this review, due to inconsistent findings among the different studies. This could be explained by urban–rural disparities in medical insurance 40.…”
Section: Discussionmentioning
confidence: 67%
“…A lack of medical insurance has been found to be a barrier to breast cancer screening participation in recent reviews10 14 39; however, evidence regarding medical insurance as a predictor of breast cancer screening participation was weak in this review, due to inconsistent findings among the different studies. This could be explained by urban–rural disparities in medical insurance 40.…”
Section: Discussionmentioning
confidence: 67%
“…Application of genomic research has the capacity to profoundly influence health outcomes, but care must be taken to ensure that all individuals have access to the benefits, and information is communicated in an ethical, culturally sensitive way (Williams, Katapodi, et al, 2016). Populations at higher risk of genetic disease are less likely to use services for a variety of reasons and are underrepresented in current genomic research (Allen, 2018;Jones et al, 2015). A review of the literature about breast cancer screening and risk assessment for young African American women found that there were opportunities for (a) increased research into the genetics of breast cancer in this population as little is known, (b) increased understanding of patient decision making regarding genetic testing as there is reluctance to participate, and (c) increased awareness of populationspecific risk factors and poor outcomes as patients were not being referred for genetic testing even though it is indicated (Jones et al, 2015).…”
Section: Involving the Publicmentioning
confidence: 99%
“…Populations at higher risk of genetic disease are less likely to use services for a variety of reasons and are underrepresented in current genomic research (Allen, 2018;Jones et al, 2015). A review of the literature about breast cancer screening and risk assessment for young African American women found that there were opportunities for (a) increased research into the genetics of breast cancer in this population as little is known, (b) increased understanding of patient decision making regarding genetic testing as there is reluctance to participate, and (c) increased awareness of populationspecific risk factors and poor outcomes as patients were not being referred for genetic testing even though it is indicated (Jones et al, 2015). Li et al (2016) found that parents considering genome-wide sequencing for their child needed more information and more psychosocial support than was provided.…”
Section: Involving the Publicmentioning
confidence: 99%
“…Benefits from clinical genetic and genomic discoveries may be especially inaccessible to healthcare consumers who have limited education and financial resources, live in areas where it is difficult to access genetic specialists, or belong to underserved populations who experience healthcare disparities (Jones, Katapodi, & Lockhart, 2015;Katapodi, Northouse, Milliron, Liu, & Merajver, 2013). The promise of scientific advancement that promotes health for everyone, as articulated in the Precision Medicine Initiative, includes the premise that patients and those who interact with the healthcare system not only will benefit from scientific advances but will also have the opportunity to form true partnerships with the scientific community to engage in research and shape agendas.…”
Section: Advocate For Patient and Family Benefitsmentioning
confidence: 99%